Oil and gas prediction basing on seismic inversion of elastic properties in Chaoshan depression, south China sea - Guangjian, Zhong; Zhongquan, Zhao; Guanghong, Tu; Kangshou, Zhang; Jing, Zhao; Hai, Yi; Changmao, Feng; Junhui, Yu (Frontiers in Earth Science, 2023)
Marine Mesozoic sediments are widely distributed in the southeastern waters of China, it is an important field of oil and gas exploration, but no oil and gas discovery has been made because of difficult to accurately understand the physical properties of Mesozoic reservoirs and predict their oil and gas properties. The conventional inversion effect is not ideal. Similar to conventional logging data (such as GR and resistivity) to divide lithology and fluid, petrophysical data (such as Poisson's ratio and density) can also divide lithology and fluid, and rock physical parameters can be obtained from prestack seismic data inversion. Using prestack seismic raw gather data to directly invert elastic parameters such as density and Poisson’s ratio and predict the development of sandstone reservoirs and hydrocarbon distribution through the results of density inversion, the Mesozoic hydrocarbon-bearing properties can be predicted. In the study area, Mesozoic sandstone reservoirs have obvious low-density characteristics, while other lithologies have high densities. The research results show that Poisson's ratio is more sensitive to hydrocarbons, and the reservoir has obvious characteristics of a low Poisson's ratio after hydrocarbon bearing. The density parameter can be used to identify sandstone reservoirs and Poisson's ratio can be used to predict the oil and gas potential. The results of seismic inversion elastic parameters show to predict oil and gas properties show that hydrocarbon anomalies have obvious characteristics, the possibility of hydrocarbon accumulation of structural A is high.